Size dependent electro-elastic enhancement in geometrically anisotropic lead-free piezocomposites. (15th September 2020) - Krishnaswamy, Jagdish A.; Rodriguez-Tembleque, Luis; Melnik, Roderick; Buroni, Federico C.; Saez, Andres
Highlights: Size-dependent flexoelectric enhancement in geometrically anisotropic lead-free piezocomposites Dramatic improvements ( 150%) in the piezo-response at dilute inclusion concentration. Flexoelectric enhancement is sensitive to the position and packing of piezoelectric inclusions within matrix. Abstract: Improving the performance of lead-free piezocomposites to the levels of state-of-the-art lead-based composites has been an important challenge in composite research. Consequently, an important agenda of piezocomposite research has been to identify new coupled mechanisms that can enhance the piezoelectric response. One such method is to tap into the size-dependent flexoelectric phenomenon in geometrically anisotropic structures. Numerical models which can account for flexoelectricity and nonlinear effects such as electrostriction are not well-developed for piezocomposite design, and current designs are based on linear piezoelectric models. Here, we develop an advanced model with flexoelectric and electrostrictive contributions in geometrically tailored piezocomposites to obtain insights on aspects of enhanced response due to small-size effects. Here, based on design considerations, we numerically demonstrate that in epoxy-matrix-based piezocomposites which are structured as truncated pyramids, flexoelectricity can lead to significant enhancements in both the electric field and the electric flux generation at small length scales. Particularly, we show that at dilute inclusion concentrations, dramatic improvements nearing 150% in the piezoelectric response are possible. Further, the flexoelectric enhancement is sensitive to the packing of the inclusions within the composite structure with the best enhancements occurring when the inclusions are closer to the inclined edges of the pyramids. We also show that in composite structures with CNT-modified matrices, flexoelectricity produces similar enhancements as in the case of unmodified matrices, demonstrating that the effect operates almost independent of nanoscale elastic and dielectric modifications by the nanotubes. Finally, we also establish that for a large range of applied stresses, the nonlinear deviations in the response due to electrostriction are negligible and flexoelectricity is the predominant size-dependent enhancement mechanism in structured lead-free piezocomposites. Graphical abstract: Image, graphical abstract